Development and validation of a personal responsibility scale for Chinese college students - Ren, Yunzhe; Wu, Jixia; Qin, Hong (Frontiers in Psychology, 2023)
Introduction: The complexity of the concept of responsibility has led to a relative lack of measuring tools. Meanwhile, the widely used measurement of conscientiousness in the Big Five personality traits suffers from inconsistencies in measuring personal responsibility. Therefore, measuring personal responsibility must be adapted to its cultural context. Spurred by these reasons, we developed a "Chinese College Student Personal Responsibility Scale" (CCSPRS) based on local theoretical foundations. Furthermore, we conducted a preliminary exploration using the new scale, examining the correlations between college students' responsibility, trust propensity, and prosocial behavior tendencies. Methods: The initial version of the scale was subjected to item analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) to form the formal version of the scale. A total of 1,038 college students were assembled. The reliability and validity of the scale were also analyzed. We collected data using the proposed CCSPRS, Interpersonal Trust Scale, and Prosocial Tendencies Measure Questionnaire and obtained 301 valid questionnaires. Results: The scale's reliability and validity indicators met the development requirements, and the investigation revealed that women students scored significantly higher in responsibility than men students. Additionally, the responsibility scores were relatively high in the first and fourth years and low in the second and third years, presenting an approximate U-shaped trend. Besides, the college students' personal responsibility, trust propensity, and prosocial behavior tendencies were positively correlated. Discussion: The proposed CCSPRS is an effective tool for measuring personal responsibility among Chinese college students. Additionally, this study analyzed the internal beliefs of individuals and concluded that personal responsibility, prosocial behavior, and trust propensity are closely interconnected, especially the relationship between responsibility and prosocial behavior.